2001
DOI: 10.2337/diabetes.50.2.270
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Islet Graft Survival in NOD Mice by Blockade of the CD40-CD154 Pathway of T-Cell Costimulation

Abstract: Allorejection and recurrence of autoimmunity are the major barriers to transplantation of islets of Langerhans for the cure of type 1 diabetes in humans. CD40-CD154 (CD40 ligand) interaction blockade by the use of anti-CD154 monoclonal antibody (mAb) has shown efficacy in preventing allorejection in several models of organ and cell transplantation. Here we report the beneficial effect of the chronic administration of a hamster anti-murine CD154 mAb, MR1, in prolonging islet graft survival in NOD mice. We explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
77
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 35 publications
5
77
0
Order By: Relevance
“…The synergy observed between Idd5 and Idd3 that results in nearly complete protection from diabetes and insulitis and increases islet allograft survival to a C57BL/6-like frequency is dependent on the B10-derived Idd5. 2 Idd3, which is partially protective of diabetes, significantly improves islet allograft survival in the NOD mouse, with the strongest effect seen in the NOD.B6 Idd3 B10 Idd5 congenic strain. The Idd3 effect likely results from differential expression of IL-2 that modulates CD4 ϩ CD25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synergy observed between Idd5 and Idd3 that results in nearly complete protection from diabetes and insulitis and increases islet allograft survival to a C57BL/6-like frequency is dependent on the B10-derived Idd5. 2 Idd3, which is partially protective of diabetes, significantly improves islet allograft survival in the NOD mouse, with the strongest effect seen in the NOD.B6 Idd3 B10 Idd5 congenic strain. The Idd3 effect likely results from differential expression of IL-2 that modulates CD4 ϩ CD25…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that Idd loci can facilitate induction of transplantation tolerance by costimulation blockade and that IL-2/Idd3 is a critical component in this process. Diabetes 58: 165-173, 2009 T he NOD mouse is a model of type 1-like autoimmune diabetes and is used to study costimulation blockade-based transplantation tolerance within the context of autoimmunity (1)(2)(3)(4). However, costimulation blockade protocols fail in NOD mice.…”
mentioning
confidence: 99%
“…Recently, increased numbers of CD40-positive microglia were detected in HIV-1-infected brain tissue (16). Because CD40 is functionally critical and nonredundant for the activation of immune responses, blocking the interaction between CD40-CD154 with anti-CD154 or CD40-Ig has been shown to be significantly beneficial in animal models of autoimmune diseases such as experimental autoimmune encephalomyelitis (17)(18)(19)(20), graft-vs-host disease (21,22), and atherosclerosis (23). These findings collectively illustrate the importance of CD40-CD154 interactions for homeostasis of immune responses.…”
mentioning
confidence: 99%
“…We have previously reported that simultaneous administration of mAb targeting CD45RB and CD154 protected islet allografts in mice and allowed for the induction of tolerance in a large proportion of recipients in a nonautoimmune background (21). In addition, monotherapy with anti-CD154 mAb significantly prolonged survival of syngeneic and allogeneic islet transplants in spontaneously diabetic NOD mice (21).…”
mentioning
confidence: 99%